2018
DOI: 10.1186/s13041-018-0368-5
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channels functionally interact with spectrin (α/β) and ankyrin B

Abstract: This study describes the functional interaction between the Cav3.1 and Cav3.2 T-type calcium channels and cytoskeletal spectrin (α/β) and ankyrin B proteins. The interactions were identified utilizing a proteomic approach to identify proteins that interact with a conserved negatively charged cytosolic region present in the carboxy-terminus of T-type calcium channels. Deletion of this stretch of amino acids decreased binding of Cav3.1 and Cav3.2 calcium channels to spectrin (α/β) and ankyrin B and notably also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…2). Regulation of Cav3 channels by such endogenous proteins would more likely reflect the numerous signalling pathways targeting Cav3 channels, as reported for the G protein βγ-dimer [50,162], calmodulin [33,86], syntaxin-1A [159], and spectrin α/β and ankyrin B [61] (Fig. 2).…”
Section: Cav3 Modulationmentioning
confidence: 77%
“…2). Regulation of Cav3 channels by such endogenous proteins would more likely reflect the numerous signalling pathways targeting Cav3 channels, as reported for the G protein βγ-dimer [50,162], calmodulin [33,86], syntaxin-1A [159], and spectrin α/β and ankyrin B [61] (Fig. 2).…”
Section: Cav3 Modulationmentioning
confidence: 77%
“…Although β- and γ-ENaC subunits consistently co-immnoprecipitate with Cav3.2 calcium channels from different neuronal tissues, we do not exclude the possibility that other protein partners are directly involved in the formation of Cav3.2 / ENaC complexes. For example, we have recently shown that Cav3.2 calcium channels can be clustered at the plasma membrane via spectrin / ankyrin B binding [26]. Spectrin is a highly abundant cytoskeletal protein in the nervous system [27, 28] and ENaC can also bind to both ankyrin and spectrin [29, 30], suggesting these cytoskeletal elements as a possible link between these channels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been long established that spectrins and integrins play important roles in the synaptic transmission (Chavis and Westbrook, 2001;Goodman, 1999), including the gating of neurotransmitter release (Featherstone et al, 2001;Huang et al, 2006). Presynaptic integrin and spectrin subtypes have been directly implicated in interactions with voltage-gated Ca 2+ channels and AZ components (Carlson et al, 2010;Garcia-Caballero et al, 2018;Khanna et al, 2007a;Khanna et al, 2007b). Nonetheless, a role for ligand-activated integrin in the synaptic recruitment of spectrin has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%